Good works! marketing and corporate initiatives that build a better world-- and the bottom line - Kotler, Philip; Hessekiel, David 1960-; Lee, Nancy 1945- (John Wiley & Sons, Inc., 2012)
"Marketing guru Philip Kotler explains how social initiatives can help your business growBusinesspeople who mix cause and commerce are often portrayed as either opportunistic corporate "causewashers" cynically exploiting nonprofits, or visionary social entrepreneurs for whom conducting trade is just a necessary evil in their quest to create a better world. Marketing and corporate social initiatives requires a delicate balancing act between generating financial and social dividends. Good Works is a book for business builders, not a Corporate Social Responsibility treatise. It is for capitalists with the hearts and smarts to generate positive social impacts and bottom-line business results.Good Works is rich with actionable advice on integrating marketing and corporate social initiatives into your broader business goals. Makes the case that purpose-driven marketing has moved from a nice-to-do to a must-do for businesses Explains how to balance social and business goals Author Philip Kotler is one of the world's leading authorities on marketing; David Hessekiel is founder and President of Cause Marketing Forum, the world's leading information source on how to do well by doing good; Nancy Lee is a corporate social marketing expert, and has coauthored books on social marketing with Philip Kotler With Good Works, you'll find that you can generate significant resources for your cause while achieving financial success"--Provided by publisher.